3 - Globalization and State–Society Relations in Africa - Mengisteab, Kidane (Africa Development, 2021)
The post-colonial African state has long been viewed as a major culprit in Afri- ca’s socioeconomic crisis. Its failure to coordinate policy with broad social inter- ests and to reconcile its governance system with the institutions and cultural values of its citizens is a major factor. This paper examines if new globalization and its liberalization policies have begun to narrow the discrepancy between policy and social interests and to facilitate the reconstitution of the state by shifting the balance of power between state and society in favor of society. The findings suggest that, despite the apparent spread of democratization during the era of post – Cold-War globalization, the policy mechanisms of globalization have notably worsened the disjuncture between policy and social interests and exacerbated the antagonisms between the state and society in the African continent.